On Cancellation Modules - Jabbar, Adil Kadir; Saeed, Dana Jamal (Sulaimani Journal for Pure and Applied Sciences, 2020)
In this paper, the concept of cancellation modules is introduced, where is a prime ideal of a commutative ring with identity, also the effect of localization on cancellation modules is studied and some properties of this type of modules are given, furthermore some conditions are given which make cancellation modules as a cancellation and conversely. Also, the effect of ascending chain conditions and descending chain conditions on the cancellation modules are studied and different characterizations of this type of cancellation modules are given.
Keywords: Multiplicative system; cancellation ideal; cancellation module; and -cancellation module